Investigating the Joint Effects of Strategy, Environment and Control Structure on Performance - Lindawati Gani; Johnny Jermias (Gadjah Mada International Journal of Business, 2011)
The purpose of this study is to investigate the effects of misfit between competitive environment, business strategy and control structure on performance. We argue that the misfit between competitive environment, business strategy and control structure has significant negative implications on shareholder value creation associated with firms’ Joint Venture formation. Based on data of publicly-traded US manufacturing firms that announce a joint venture formation, we found that firms that have perfect fit are valued higher than those with both strategy and structural misfits and also those with structural misfit. Contradictory results were found when comparing firms with perfect fit with those that have strategy misfit. Further analyses indicate that all those strategy misfit firms operate in high entry barriers, where firms can compete effectively using either innovation or cost efficiency strategy due to the fact that they possess resources that are difficult to be imitated by their competitors.